Effect of mid-roll video advertising value and perceived intrusiveness on Facebook viewers' response: the mediating roles of attitude and word-of-mouth intention - Jakkrit Thavorn; Puripat Trichob; Worasak Klongthong; Chittipa Ngamkroeckjoti (Cogent Business & Management, 2022)
Advertising plays an essential role for creating brand awareness that leads to consumer behavior toward services and products. The objective of this research is to investigate the role of mid-roll video advertising regarding its perceived intrusiveness and value on viewers' response to those ads. Data from 200 users who have experienced mid-roll video advertising were analyzed in a two-step method via structural equation modeling (SEM) and confirmatory factor analysis (CFA). The indirect impacts were investigated and compared via the bootstrap approach. The analysis confirms that the value of mid-roll video advertising is significantly and positively associated with attitude toward mid-roll video advertising and word-of-mouth (WOM) intention. In addition, the positive connection between WOM intention and attitude as well as viewers' response are observed. However, the negative association between perceived intrusiveness and attitude is found as well in this research. For the contributions, the result not only strengthens the importance of the advertising value theory as a framework to explain the impact of advertising, but also provides recommendations for advertisers and content creators regarding some managerial actions that may need to be taken in order to satisfy consumers.
Keywords: 650; attitude; Facebook; mid-roll advertising value; online ads; perceived intrusiveness; Thailand; viewers response; word-of-mouth intention